Предмет: Алгебра, автор: fuks81

Решите пожалуйста
 {x}^{2} - 6 + 5 = 0
 {2x}^{2} - 5x + 4 = 0
 {3x}^{2} - 6x + 2 = 0

Ответы

Автор ответа: aliyas1
0

 {x}^{2} - 6x + 5 = 0 \\  x_{1} +  x_{2} = 6 \\ x_{1}  \times   x_{2} = 5 \\ x_{1}  = 1 \\  x_{2} = 5 \\ Ответ: (1; \: 5) \\  \\ </p><p>{2x}^{2} - 5x + 4 = 0 \\ D=25 - 4 \times 2 \times 4 =  - 7</p><p> \\  \\ Ответ: действ.корней \:  \:  нет \\  \\ {3x}^{2} - 6x + 2 = 0 \\ D = 36 - 4 \times 3 \times 2 = 12 \\ x_{1}  =  \frac{6 -  \sqrt{12} }{2 \times 3}  =  \frac{6 - 2 \sqrt{3} }{6} =  \\  =  \frac{3 -  \sqrt{3} }{3}  \\  x_{2} = \frac{3  +   \sqrt{3} }{3}  \\ Ответ: (\frac{3 -  \sqrt{3} }{3}; \: \frac{3  +   \sqrt{3} }{3})

Похожие вопросы
Предмет: Математика, автор: Аноним
Предмет: Математика, автор: данил1257